(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2004)
The author of this text examines the issues related to human rights, especially the expression of own identity of ethnic Macedonians in Greece, and the nonrecognition by the official Greek state administration. The author makes a detailed analysis on the situation with minorities and their rights in other European countries and the neighboring countries of Greece. He focuses upon the awareness of the fact that national states at the Balkans misuse minorities, presenting them as a basic destabilizing factor in the region.